Effect of replacement of shell grit with stone grit in diet onproduction performance and mineral retention in Namakkal Gold Quail - PREMKUMAR, K; KANNAN, D; VASANTHAKUMAR, P; RAJENDRAN, K; RAMAKRISHNAN, S; KANNAN, V (The Indian Journal of Animal Sciences, 2026)
The present study was undertaken to evaluate the feasibility of using stone grit as an alternative calcium source in diet of egg type Japanese quail. A biological trial was conducted by using 360 of five week old female “TANUVAS Namakkal Gold quail” strain, divided into five dietary treatment groups, by replacing shell grit with 2 mm and 4 mm stone grit at 50 and 100 per cent levels in the diet. The study was conducted for 52 weeks, monitoring production performance (body weight, egg production, feed intake, feed efficiency, defective shelled eggs per cent, livability, leg abnormalities) and economic efficiency for every 28 days period. A metabolic trial was conducted for 5 days at the end of 52 weeks to assess the dry matter, calcium and phosphorous retention. Replacement of shell grit with stone grit (2 mm and 4 mm) at both inclusion levels had no significant impact on egg production, egg mass, feed efficiency, defective shelled eggs per cent and livability for the overall experimental period. The overall feed consumption was significantly (p≤0.05) higher in 100 per cent 2 mm stone grit fed group and the calcium and phosphorous retention were significantly(p≤0.05) higher in 50 per cent 2mm stone grit fed group. It may be concluded that replacement of shell grit with stone grit improved the feed consumption, calcium and phosphorous retention without affecting egg production and feed conversion, supporting the use of stone grit as an efficient alternative calcium source in the diet of egg type quails.